PENGARUH MEDIA FLASHCARD BERBASIS AUGMENTED REALITY TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATERI ORGAN PENCERNAAN MANUSIA KELAS V SD NEGERI 1 PAGAR AIR - Dwi Sartika; Mislinawati; Tursinawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low learning outcomes of students in the human digestive organs subject in fifth grade at SD Negeri 1 Pagar Air, which is caused by the lack of use of engaging and innovative learning media. The use of appropriate learning media is expected to help students understand the material more easily and improve learning outcomes. One such media is Augmented Reality-based flashcards, which can display objects realistically and interactively. This study aims to determine the effect of using Augmented Reality-based flashcards on the learning outcomes of fifth grade students at SD Negeri 1 Pagar Air. This study used a quantitative approach with a Quasi-Experimental Design with a Pretest–Posttest Control Group Design. The research sample consisted of two classes: an experimental class using Augmented Reality-based flashcards and a control class using video learning. Data collection was conducted through learning outcome tests in the form of pretests and posttests. Data were analyzed using statistical tests. The results showed that the average pretest score for the experimental class was 46.36, increasing to 88.73 in the posttest. Meanwhile, the average pretest score for the control class was 36.52, increasing to 79.48 in the posttest. The results showed a significance value (Sig. 2-tailed) of 0.000 < 0.05, thus concluding that the use of Augmented Reality-based flashcards significantly impacted the learning outcomes of fifth-grade students at SD Negeri 1 Pagar Air on the topic of human digestive organs.